Enhancing business performance in the power generation industry: Exploring determinant factors through operational turnaround strategies (Global Business Management Review (GBMR), 2023)
This research examines the implementation of operational turnaround strategies in a power generation company to enhance the organization's business performance. The company seeks to increase the profitability of its assets by improving operational efficiency. Operational turnaround strategies, including cost reduction, revenue generation, and asset reduction, were implemented in the company to achieve operational excellence and revitalize underperforming assets. This study aims to determine the extent of operational turnaround strategy implementation, evaluate its impact on business performance, and fill existing research gaps. A self-administered questionnaire was distributed to 102 personnel involved in the company 's turnaround program, including experts, managers, and power plant engineers. The collected data were analysed using Statistical Package for Social Science (SPSS) software. The findings indicate a positive relationship between the implemented operational turnaround strategies and the company's business performance. This study provides valuable insights for the power generation industry, emphasizing the significance of effective asset management practices to enhance business performance. By implementing operational turnaround strategies, organizations can optimize operational efficiency and increase profitability. The findings contribute to closing the research gap on the link between business performance and operational turnaround strategies. The company and other power generation companies can utilize the practical implications from this study to guide their efforts in achieving operational excellence and maximizing profitability.